2014
DOI: 10.19173/irrodl.v15i5.1854
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of learner intent and behaviour in live and archived MOOCs

Abstract: The advent of massive open online courses (MOOCs) has created opportunities for learning that are clearly in high demand, but the direction in which MOOCs should evolve to best meet the interests and needs of learners is less apparent. Motivated by our interest in whether there are potential and purpose for archived MOOCs to be used as learning resources beyond and between instructor-led live-sessions, we examined the use of a statistics MOOC and a computer science MOOC, both of which were made available as ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 16 publications
(9 reference statements)
1
27
0
1
Order By: Relevance
“…The findings indicate that fifteen articles adopted two research methods in the data collection process. Typically, articles adopting two research methods combined the use of surveys with interviews [20]- [25] or with log files extracted from MOOC platforms [26]- [30]. Beyond that, very few articles adopted three or more research methods for data collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings indicate that fifteen articles adopted two research methods in the data collection process. Typically, articles adopting two research methods combined the use of surveys with interviews [20]- [25] or with log files extracted from MOOC platforms [26]- [30]. Beyond that, very few articles adopted three or more research methods for data collection.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception is one research piece which addressed both participants' and instructors' perceptions of quality design of MOOCs [33]. The sample size in a single study ranges from 49 students [21] to more than 50,000 participants [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campbell, Gibbs, Najafi & Severinski (2014) found that students had significant interest in the live online courses, and they depended on archived online courses to use as reference sources. In addition, they indicated that their results showed the significant potential for online courses to be very useful, as they combine the most valuable features of archived and live MOOCs to meet the interests and needs of the learners.…”
Section: Resultsmentioning
confidence: 99%
“…Followings <Table 1> are hypothetical constructs per the fundamental definitions. [4], [8], [15], [19] Emphasizing learning environment focused on interaction away from traditional online education a method of MOOC planning and realizing learning environment [6], [8], [14], [16], [19] Changing and Evolving Education System focused on learners factors needed for learning continuity [2], [3], [6], [8], [11], [14] A role of destructive innovation for existing education system a role of MOOC improving existing education system [7], [18], [19] Providing high quality courses to anyone in the dimension of lifelong education a direction of practice in the national and personal dimension [2], [8], [10], [12], [19] 3. Method…”
Section: Issues Of Mooc Participationmentioning
confidence: 99%